2023
DOI: 10.1002/uog.26077
|View full text |Cite
|
Sign up to set email alerts
|

Vascular phenotype at 35–37 weeks' gestation in women with gestational diabetes mellitus

Abstract: Objectives To examine the vascular phenotype at 35–37 weeks' gestation of women with gestational diabetes mellitus (GDM) and compare it to that in women without GDM, using ophthalmic artery Doppler and carotid–femoral pulse‐wave velocity. Methods This was a prospective observational study of women attending for a routine hospital visit at 35 + 0 to 37 + 6 weeks' gestation. This visit included recording of maternal demographic characteristics and medical history, ophthalmic artery Doppler for calculation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Our finding of increased AIx among women with GDM is in agreement with a number of previous studies 7,10 but is at odds with others 6,8,9 . This contrast in findings may be explained by differences in study design.…”
Section: Interpretation Of Main Findings and Comparison With The Lite...supporting
confidence: 90%
See 4 more Smart Citations
“…Our finding of increased AIx among women with GDM is in agreement with a number of previous studies 7,10 but is at odds with others 6,8,9 . This contrast in findings may be explained by differences in study design.…”
Section: Interpretation Of Main Findings and Comparison With The Lite...supporting
confidence: 90%
“…The three studies whose findings are at odds with those of our study examined AS at a single timepoint in the third trimester and two of them 6,9 included fewer than 35 women with GDM. Mansukhani et al 8 . included a larger number of women but examined AIx at 35–37 weeks, which straddles two gestational‐age windows of our study, including the ≥ 36 + 0‐week window, at which we also found no significant difference between women with GDM and healthy controls.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations